2014
DOI: 10.1007/s00018-014-1589-0
|View full text |Cite
|
Sign up to set email alerts
|

ZEB2-transgene expression in the epidermis compromises the integrity of the epidermal barrier through the repression of different tight junction proteins

Abstract: Epithelial homeostasis within the epidermis is maintained by means of multiple cell-cell adhesion complexes such as adherens junctions, tight junctions, gap junctions, and desmosomes. These complexes co-operate in the formation and the regulation of the epidermal barrier. Disruption of the epidermal barrier through the deregulation of the above complexes is the cause behind a number of skin disorders such as psoriasis, dermatitis, keratosis, and others. During epithelial-to-mesenchymal transition (EMT), epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…For this purpose, NK cell maturation intermediates were defined as shown in Fig. 1 Tg/Tg mice (Tatari et al, 2014). These genetic modifications allow selective inactivation of Zeb2 or transgenic (Tg) Zeb2 expression from the Rosa26 promoter in NK cells, respectively.…”
Section: Res Ults and Discussion Zeb2 Is Essential For Nk Cell Matumentioning
confidence: 99%
“…For this purpose, NK cell maturation intermediates were defined as shown in Fig. 1 Tg/Tg mice (Tatari et al, 2014). These genetic modifications allow selective inactivation of Zeb2 or transgenic (Tg) Zeb2 expression from the Rosa26 promoter in NK cells, respectively.…”
Section: Res Ults and Discussion Zeb2 Is Essential For Nk Cell Matumentioning
confidence: 99%
“…19 In addition to the already large number of TJ proteins identified in human or mouse epidermis, some TJ proteins have been identified only in cultured keratinocytes ( Table 2). Further studies are needed to 118 were also found in the SC of mice. determine their expression patterns in a fully developed mature epidermis.…”
Section: Tj Composition and Function In Healthy Skin (And Cultured Kementioning
confidence: 98%
“…claudins 1, 7, and 12, Junctional Adhesion Molecule (JAM)-A, and MUPP1), or to the spinous keratinocytes (e.g., ZO-1, ZO-2, claudins 4, 6, 18). [26][27][28]35,[57][58][59][60][61][62] Similar to observations in cultured keratinocytes, disruption of cadherin-containing adherens junctions in vivo results in impairment in tight junction formation. Targeted inactivation of Cdh1 in mice, which encodes E-cadherin, results in extensive transepidermal water loss and loss of functional tight junctions in the stratum granulosum.…”
Section: Cingulinmentioning
confidence: 96%